The health and wellbeing of Australian social housing tenants compared to people living in other types of housing - Megan Freund; Matthew Clapham; Jia Ying Ooi; David Adamson; Allison Boyes; Robert Sanson-Fisher (BMC, 2023)
Abstract Background Although social housing provides access to safe and affordable housing, recent studies have found that social housing tenants consistently have lower levels of health and well-being compared to other people. Given this, there is a need to examine multimorbidity for social housing tenants. Methods Secondary data analysis of the 2017-18 Australian National Health Survey (n = 14,327) compared the health of adults residing in social housing compared to people in other housing types (private rentals, homeowners, and homeowners/mortgagees). Results Most health factors examined were more prevalent in social housing tenants compared to those living in other housing types. Individual health problems identified as more highly prevalent in social housing tenants compared to all other housing types included mental health issues (43%), arthritis (36%), back problems (32%), hypertension (25%), asthma (22%) and COPD (11%). 24% of social housing tenants reported five or more health factors compared to 3-6% of people in other housing types. Conclusions Although these findings are not unexpected, they provide more detailed evidence that social housing providers and policy makers should consider when planning future initiatives.